Enhanced electrical conductivity and mechanical stability of flexible pressure-sensitive GNPs/CB/SR composites: Synergistic effects of GNPs and CB. Issue 22 (2nd November 2015) - Liu, Ping; Huang, Ying; Liu, Caixia; Wang, Yue; Guo, Xiaohui; Zhang, Yugang; Ge, Yunjian
Abstract: Abstract : Silicone Rubber (SR) filled with graphene nanoplatelets (GNPs) and carbon black (CB) is prepared for high performance flexible pressure sensor. Due to the synergetic effect of mixed GNPs and CB, the percolation threshold of GNPs/CB/SR is lower than that of CB/SR, which indicates the addition of GNPs is contributed to enhance the electrical conductivity of GNPs/CB/SR. Moreover, the GNPs/CB/SR has a higher electrical stability and weaker resistance creep than that of GNPs/SR. That is to say, the addition of CB can promote the electrical and mechanical performance of GNPs/CB/SR, simultaneously. The pressure sensor array based on GNPs/CB/SR with weight on different sensing element is tested, and the results show that the size of applied loading on the pressure-sensitivity array can be recognized accurately.